Transdisziplinäre Realexperimente und künstlerische Forschungspraktiken. Koproduktion urbaner Resilienz im Reallabor Gängeviertel in Hamburg - Ziehl, Michael (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
Using real-world laboratories, researchers in spatial sciences increasingly engage in both, shaping and observing transformation processes of urban systems. Thereby, real-world experiments are critical. As interventions into the real, they serve to test and foster possibilities of change. This paper discusses two real-world experiments with reference to the Gängeviertel in Hamburg. Their purpose was to shape the conflictual cooperation process to renovate the historic inner city quarter in a more efficient way and to gain knowledge about motives and values of those who are involved. The paper focusses on arts-based practices such as staging, arranging and performing, that were integrated into the research design with the purpose to outline their potentials for transformative research as well as to discuss challenges and constraints. Furthermore the scientific assumptions of the research design are illustrated.